Robert Gruenewald letter to Thomas H. Kent regarding details on fall bird sightings, December 7, 1998 - Gruenewald, Robertet al (1998)
Letter from Robert Gruenewald to Thomas H. Kent regarding details on fall bird sightings, December 7, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed/flatbed